2007
DOI: 10.1242/jeb.004648
|View full text |Cite
|
Sign up to set email alerts
|

Escape performance decreases during ontogeny in wild crickets

Abstract: SUMMARY Increasing the ecological relevance of studies relating to the performance of organisms has been a central issue for functional biologists over the last few years. Of particular concern are changes in performance throughout the life cycle as selective forces act differently on various life stages. We addressed this issue experimentally by following ontogenic variations in the escape performance of crickets threatened by artificial predatory signals. We measured their performance under na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…In the only other study of locomotor ontogeny in birds (chukar partridges), WAIR performance increased with age and was correlated with morphological and kinematic changes early in development (8 -20 days; [7]). However, there are few known examples where young outperform adults in escaperelevant behaviours: jackrabbits (Lepus; [4,5]), lizards (Anolis, [6]), crickets (Nemobius sylvestris [30]), brush turkeys (this study). It is likely that such developmental strategies evolved in response to high predation early in life (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…In the only other study of locomotor ontogeny in birds (chukar partridges), WAIR performance increased with age and was correlated with morphological and kinematic changes early in development (8 -20 days; [7]). However, there are few known examples where young outperform adults in escaperelevant behaviours: jackrabbits (Lepus; [4,5]), lizards (Anolis, [6]), crickets (Nemobius sylvestris [30]), brush turkeys (this study). It is likely that such developmental strategies evolved in response to high predation early in life (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…1A). The velocity and acceleration of the piston were accurately controlled using a computer (for more details see Dangles et al, 2006bDangles et al, , 2007. Two spot lights placed above the arena provide homogeneous illumination (2 spots of 230 V, 100 W white light).…”
Section: Experimental Devicementioning
confidence: 99%
“…Fortunately, the last decade has witnessed an explosion of mobile and wireless technology that enables researchers to literally take the "laboratory into the field," and some sensory ecology research has already felt the advantage of these technological changes (e.g., vision research [Fleishman et al 1998 [Barth et al 1995;Dangles et al 2007]). This potential distinc- Frequency of eye cone classes were measured at different developmental stages in wild-caught black bream (Acanthopagrus butcheri) reared under two different lighting conditions.…”
Section: Future Challenges Taking the Lab To The Fieldmentioning
confidence: 99%
“…In particular, this research showed that the loss of sound signals outdoors, especially when insects call within stands of vegetation, has forced insects to compensate by adapting specific behaviors such as redundancy calls or chorusing. More recently, Dangles et al (2007) used a portable simulator of spider air-flow signals to measure the sensory-mediated escape performance of crickets under field conditions ( Figure 4A, B). This experiment revealed that both the behavior and performance of evading crickets in nature, as well as the sensory pathways involved in such escape behavior, differ in several ways from observed laboratory performance.…”
Section: Future Challenges Taking the Lab To The Fieldmentioning
confidence: 99%
See 1 more Smart Citation